BENEFITS OF USING TECHNOLOGY IN EDUCATION - Bakhronova M.A,; Doniyorova Nigora,; Vohidova Mehrangi, (Лучшие интеллектуальные исследования, 2023)
Abstract: This paper gives information about using technology in education during the lessons. Research has shown that integrating technology into the education system can have numerous benefits for both students and teachers. It aims to ensure inclusive and equitable quality education for all. Digital technologies have emerged as an essential tool to achieve this goal. These technologies are simple to detect emissions sources, prevent additional damage through improved energy efficiency and lower-carbon alternatives to fossil fuels, and even remove surplus greenhouse gases from the environment.